2017
DOI: 10.4236/ijmpcero.2017.64032
|View full text |Cite
|
Sign up to set email alerts
|

Method for Converting Cone-Beam CT Values into Hounsfield Units for Radiation Treatment Planning

Abstract: Cone-beam CT (CBCT) images acquired during radiation treatment can be used to recalculate the dose distribution as well as to confirm the treatment location. However, it is difficult to obtain the electron densities (EDs) necessary for dose calculation from CBCT images because of the effects of scatter contamination during CBCT image acquisition. This paper presents a mathematical method for converting the pixel values of CBCT images (CBCT values) into Hounsfield units (HUs) of radiation treatment simulation C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…CT values of the original CBCT images may fluctuate for the same material in the different relative positions being scanned in the image volume 15 . In Table 1 , the CT values of the generated CBCT from Cycle-Deblur GAN showed better results than those from RED-CNN and CycleGAN in the breast, lung, muscle, mediastinum, and sternum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT values of the original CBCT images may fluctuate for the same material in the different relative positions being scanned in the image volume 15 . In Table 1 , the CT values of the generated CBCT from Cycle-Deblur GAN showed better results than those from RED-CNN and CycleGAN in the breast, lung, muscle, mediastinum, and sternum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, noise and scatter are well known to produce additional artefacts 14 . However, the CT values in CBCT images may fluctuate because of scattering contamination, depending on the shape, positioning, size, and inner tissue structure 15 , 16 . The original CT values of CBCT could not be used for dose calculation unless some correction methods were applied 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Derksen et al improved the deformation field registration method and constrained the deformation area by adding the OAR contours acquired by the image segmentation method, to improve registration accuracy between CBCT and CT sim images (14). Abe et al established the greyscale linear relation between CBCT and CT images by the histogram-matching method to correct Hounsfield unit (HU) values in CBCT images, and the experimental results showed that CBCT images after histogram matching could be applied to therapeutic plan formation of cervical and prostatic cancer (15). Although this type of method can correct HU information in the CBCT image, it has high accuracy requirements for the image registration algorithm and matching method, and the setting of an objective function is also complicated.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome interference due to motion in the breathing cycle and patient weight loss [106], cone-beam CT (CBCT) is commonly used for target position verification and setup displacement correction to avoid suboptimal target coverage and excessive doses to organs at risk. However, raw CBCT data cannot be used for SBRT dosage calculation due to considerable artifacts such as streaking and shading [107][108][109] caused by scatter contamination, resulting in different Hounsfield unit (HU) values from CT scans [110]. To improve the HU fidelity of CBCT, Liu et al [95] utilized self-attention cycleGan-based CBCT to synthetic CT (sCT) models on a dataset consisting of 30 patients previously treated with pancreas SBRT at Emory University.…”
Section: Improvement Of Image Qualitymentioning
confidence: 99%